63 Characterizing Organizational Risk Factors and Clinical Impacts of Unplanned Extubations among Infants in the Neonatal Intensive Care Unit. (29th October 2021) - Le Blanc, Gabriella; Jabbour, Elias; Patel, Sharina; Zeid, Marco; Shalish, Wissam; Kazansteva, Olga; Beltempo, Marc
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Organizational factors in neonatal intensive care units (NICUs) can increase the risk of adverse events, such as unplanned extubations (UPEs). UPE is the premature and unanticipated removal of an endotracheal tube. UPE and subsequent reintubation may increase the risk for lung injury and bronchopulmonary dysplasia (BPD) among preterm infants. Objectives: First, we aimed to assess the association between daily nursing overtime and UPEs in the NICU. Second, we aimed to evaluate the association between UPE, re-intubation after UPE, and BPD in the sub-group of infants born < 29 weeks' gestational age (GA). Design/Methods: We conducted a retrospective cohort study including infants admitted to a tertiary care NICU between 2016-2019. Daily nursing hours were obtained from local administrative databases. Patient data was collected from the local Canadian Neonatal Network database. Association between ratio of daily nursing overtime hours/total nursing hours (OTR) was compared between days with and without UPEs, using logistic regression analyses. Associations between UPE and BPD among infants born <29 weeks requiring mechanical ventilation was evaluated in a 1:1 propensity-score matched (PSM) cohort. Infants were matched based on GA ± 2 weeks, mechanical ventilation days at time of UPE ± 5 days and SNAPII>20. Results: There were 108/1370 (7.8%) days with ≥ 1 UPE, for a total of 116 UPE events from 87 patients (23-42 weeks GA). Higher median OTR was observed on days with UPE compared to days without (3.3% vs. 2.5%, p=0.01). OTR was associated with higher adjusted odds of UPE (aOR 1.09, 95% CI 1.01-1.18), while other organizational variables were not (Table 1). Among ventilated infants <29 weeks' GA (n=XX), UPE rate was 31% (59), BPD rate was 42% (81) and re-intubation rate after UPE was 59% (35). In the PSM cohort of infants <29 weeks, re-intubation after UPE, was associated with increased length of mechanical ventilation (aOR 16.45; CI 6.18, 26.72) as well as increased odds of BPD, when compared to infants not requiring re-intubation (aOR 4.97, 95% CI 1.54-18.27) (Table 2). Conclusion: Higher nursing overtime was associated with increased UPEs in the NICU. Re-intubation was frequently required after a UPE. Among the infants born < 29 weeks' GA, UPE requiring reintubation was associated with increased total length of mechanical ventilation and increased risk of BPD. Our findings highlight the role of workforce management in improving outcomes in the NICU, through reducing the incidence of UPEs.